Search-Theoretic Models of Organization Control by Budgeted Multiple Goals - Charnes, A.; Stedry, A. C. (Management Science, 1966)
Models of situations in which individuals are faced with multiple activities among which they must allocate their effort are postulated. Optimal allocations are found for four assumed motivational structures—profit maximization and three involving performance goals in each of the activities. Heuristic approximations to the optimal allocations are developed. Also, the relationships between the various motivation structures are explored.